Chemical Distribution of Phosphorus in Soils used during the Development of Sorption Isotherms - Schmitt D.* (2017)
© Soil Science Society of America. This is an open access article distributed under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).This study was developed to provide initial information on the chemical distribution of P into the different soil P pools after a soil sample underwent P sorption using 17 soil samples from the United States (13) and Brazil (4). During the sorption phase, soil samples were equilibrated with solutions containing increasing P concentrations (0–75 mg P L–1) following standard procedures. Following the sorption phase, the soil samples were allowed to air dry for 72 h and underwent a chemical fractionation (in water, anionic resin, 0.5M NaHCO3, 0.1M NaOH, and 1.0M HCl). A wide range of sorption strength ranging from 0.043 to 0.289 L kg–1 and a maximum sorption ranging from 189 to 789 mg kg–1 were observed. More than 59% of the sorbed P was found in the water + resin fraction, which is considered the most labile pools where the binding energy is assumed to be low. In contrast, less than 25% of the sorbed P was found in the nonlabile pools where the binding energy is assumed to be the greatest. Although less than 25% of the sorbed P was found in the non-labile pools, the NaOH+HCl fraction contributed 2 to 61% of the overall sorption strength estimated for the soils studied. The results of this study suggest that sorption strength calculated from sorption studies are heavily skewed toward the nonlabile fraction, which was found to constitute a very small portion of the binding sites occupied during sorption studies.